Una especie nueva de Ipomoea (Convolvulaceae), de los estados de Guanajuato, Hidalgo y Querétaro, México - Carranza Gonzalez, Eleazar; Zamudio Ruiz, Sergio; Murguia Sanchez, Guillermina (Instituto de Ecología, A.C., 1998)
Ipomoea rzedowskii is described as a new species to science, from the Mexican states of Guanajuato, Hidalgo and Querétaro. This white flowered shrub grows in xerophilous shrublands on steep slopes east of Xichú and in the canyons of Estórax, Moctezuma and Tolimán rivers. This new taxon belongs to the series Arborescentes.